2007
DOI: 10.1055/s-2007-986680
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pregnancy after Radical Trachelectomy: Case Reports and Systematic Review of the Literature

Abstract: This article reviews the existing literature on pregnancy outcomes following radical trachelectomy for low-stage cervical carcinoma and describes the guidelines in our institution for obstetrical management after managing two pregnancies following radical trachelectomy. We performed a literature search in PUBMED, MEDLINE, and EMBASE for the keywords "radical trachelectomy," "pregnancy," or "fertility" from 1994 to the present. All observational studies were included, and duplicate cases were excluded from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 21 publications
1
59
0
7
Order By: Relevance
“…According to the review by Jolly et al [8], the preterm delivery rate after RT was 49 in 200 (24.5%), and 14 of the 49 (29%) preterm deliveries \37 weeks of gestation were preceded by pPROM, which is clearly higher than reported for the general population. The cause of such adverse pregnancy outcomes is believed to be vaginal and uterine cervical infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the review by Jolly et al [8], the preterm delivery rate after RT was 49 in 200 (24.5%), and 14 of the 49 (29%) preterm deliveries \37 weeks of gestation were preceded by pPROM, which is clearly higher than reported for the general population. The cause of such adverse pregnancy outcomes is believed to be vaginal and uterine cervical infection.…”
Section: Discussionmentioning
confidence: 88%
“…A recent review of the published literature totaling more than 600 cases confirmed an overall recurrence rate of\5% and death rate of \3% [8]. However, it is well known this treatment modality is associated with a variety of adverse pregnancy outcomes, including second trimester loss, pPROM, and the subsequent occurrence of preterm delivery [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the patients was 34 years (interquartile range [IQR], 30-37 years). The median body mass index (BMI, calculated as weight in International Journal of Gynecology and Obstetrics 109 (2010) 37-40 kilograms divided by the square of height in meters) was 22 (IQR,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). No patient presented with inherited thrombophilias.…”
Section: Methodsmentioning
confidence: 99%
“…The reproductive outcomes of the radical trachelectomy are promising. Approximately two thirds of patients are able to conceive, and the rate of preterm deliveries is approximately 25% [3,4].…”
Section: Introductionmentioning
confidence: 99%